2018
DOI: 10.2166/wcc.2018.155
|View full text |Cite
|
Sign up to set email alerts
|

Trends and changes detection in rainfall, temperature and wind speed in Burundi

Abstract: This paper assessed the potential impacts of trends detected in rainfall, temperature and wind speed on hydro and wind power resources in Burundi. Two climatic stations located at two contrasting regions, namely Rwegura catchment and northern Imbo plain, were considered. Rainfall, temperature and wind speed observed data were considered for the period 1950–2014 and future projection data from seven Regional Climate Models (RCMs) for the period 2021–2050 were used. The interannual variability analysis was made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 20 publications
5
25
0
Order By: Relevance
“…The findings from this study projecting increase in WS which implies increase in WPD are consistent with many studies from different regions of the globe as well as studies from East Africa [2] [45] [46] [47] [48]. Indeed, Lawin et al [15] reported increasing trend in wind speed at Northern Imbo plain while Collins et al [14], predicted that Burundi would experience more extreme weather conditions in the future characterized by high winds; which is consistent with our findings.…”
Section: Future Wind Speed Potential On Different Heights In Thesupporting
confidence: 92%
See 3 more Smart Citations
“…The findings from this study projecting increase in WS which implies increase in WPD are consistent with many studies from different regions of the globe as well as studies from East Africa [2] [45] [46] [47] [48]. Indeed, Lawin et al [15] reported increasing trend in wind speed at Northern Imbo plain while Collins et al [14], predicted that Burundi would experience more extreme weather conditions in the future characterized by high winds; which is consistent with our findings.…”
Section: Future Wind Speed Potential On Different Heights In Thesupporting
confidence: 92%
“…In fact, at significance level equals to 0.05, the Kendall's tau of 0.31, 0.38, 0.36 and 0.49 with their respective p-values equal to 0.0098, 0.0016, 0.0033 and < 0.0001 were revealed at NHL, NIP, SHL and SIP, respectively. This increasing trend in wind speed is consistent with the findings in many studies from the East Africa [15] [43]. Figure 10 presents the monthly distribution of wind power density (WPD) over the reference period 1981-2010.…”
Section: Wind Speed Interannual Variabilitysupporting
confidence: 87%
See 2 more Smart Citations
“…Such an absence of significant trend in rainfall is also reported by N'Tcha M'Po et al [40] in Ouémé river basin by 2050, using a REMO model. Similarly, Lawin et al [42] reported no trend in rainfall pattern in the Imbo north plain region in Burundi under central Africa climatology using an ensemble of eight regional climate models. The SPI computed for each region emphasizes this variability ( Figure 5).…”
Section: Future Rainfall Patternmentioning
confidence: 96%